Dinamika Nitrogen dan Hasil Tanaman Padi Sawah (Oryza sativa L.) Kultivar INPARI 31 akibat Pemupukan NPK 18:8:18 dan Penggenangan Air pada Fluvaquentic Epiaquepts - Rija Sudirja; Encep Hidayat Salim; Ade Setiawan; Muhammad Farghan Fauzan (Fakultas Pertanian Universitas Padjadjaran, 2017)
Fertilizer is one of the crucial means to improving rice productivity. The purpose of this research is to know and understand the behavior of nitrogen in the soil and plant rice (Oryza sativa L.) as well as the highest yields in Fluvaquentic Epiaquepts. This study was conducted in May through September 2015 at the Experimental Garden of Soil and Water Management, Faculty of Agriculture Padjadjaran University, Jatinangor, Sumedang regency. The altitude of place was 725 meters above sea level. The study design used randomized block design (RAK) with ten treatments, various dosage level of NPK 18:8:18 combined with the setting puddles and three replications, thus totaling thirty experimental plots. The results showed a real effect due to the provision of various level dose of NPK 18:8:18 and combinations of settings puddles on plant growth, the content of soil-N, absorption-N, and rice yields, both at the time of vegetative end as well as post-harvest rice. In addition, treatment of NPK 18:8:18 by setting a puddle able to deliver the highest yield at the time of post-harvest each by N-total of 0,64%; N-organic 0,26%; N-NH4 0,11%; N-NO3 0,31%; and absorption-N of plants by 1,80%. This resulted in a relatively high yield of 9.952 kg.ha-1, but not significantly different from NPK doses of 450 and 600 kg.ha-1.Keywords: NPK doses, soil-N, absorption-N, rice yield